Plan de Mejora del proceso de gestión para las organizaciones económicas populares y solidarias. Caso: Asociación de Producción Cafetalera del Sur Oriente de la provincia de Loja periodo 2016-2021 - Ávila Jiménez, Juan Fernando (2023)
This article analyzes the internal management model of popular and solidarity economic organizations; and according to the results obtained, an Improvement Plan is presented that can favor the best development of its activities. The study was carried out in the Association of High-Altitude Coffee Producers of the South East of the province of Loja, which brings together 198 coffee families from the cantons Espíndola, Quilanga, Calvas and Gonzanamá. The results showed that there is no adequate training of its leaders and administrative staff, undemocratic and ineffective accountability mechanisms, low production, and productivity of coffee per hectare and deficient associative marketing. The use of a descriptive analytical methodology allowed to obtain varied criteria by the partners of the organization, managerial and administrative staff, which served as a basis for the fulfillment of the object of the research.